THE KYRGYZ REPUBLIC: A NEW POLITICAL REALITY - MIRSAYITOV, Ikbalzhan (CENTRAL ASIA AND THE CAUCASUS, 2011)
On 7 April, 2010, President of Kyrgyzstan Kurmanbek Bakiev was removed. The Kyrgyz Republic lived through a second regime change, a unique event in the history of Central Asia. An Interim Government headed by Rosa Otunbaeva was put together by the leaders of 14 opposition parties, the most prominent among them being O. Tekebaev (Ata-Meken), A. Atambaev (Social-Democratic Party of Kyrgyzstan), T. Sariev (Ak-Shumkar), A. Beknazarov (United People’s Movement), and E. Kaptagaev (Uluu Birimdik). The new government described itself as “usurpers” and “dictators.”1The Interim Government disbanded the legislative and executive power branches, as well as all the ministries and the bureaucracy, to concentrate power in its hands. This caused a political default and stirred up a lot of trouble in the country’s south.Between 13 and 19 May, supporters of the former president made an aborted attempt in the Osh, Jalal-Abad, and Batken regions to recapture power in the south. This resulted in the arrest of Usen Sydykov, former head of the Administration of the KR President in 2005-2006, and Iskhak Masaliev, head of the Party of Communists of Kyrgyzstan. The country house of Bakiev’s family in the village of Teyit was burned down when supporters and opponents of the former president clashed in the Jalal-Abad Region; several people were killed.Between 10 and 16 June, ethnic clashes between Kyrgyz and Uzbeks in the cities of Osh and Jalal-Abad developed into bloodshed. According to official data, 423 were killed and about 2 thousand private houses were damaged (1,690 of them were totally destroyed).Despite the political instability and tragic events in the south, the Interim Government convened the Constitutional Assembly to amend the Constitution and transform the presidential republic into a parliamentary one. The constitutional changes called for a national referendum to be held on 27 June, 2010.On the eve, about 100 thousand Uzbeks (citizens of the Kyrgyz Republic) were in the Republic of Uzbekistan as “temporary migrants,” while Kyrgyz left the zone of conflict to join their relatives elsewhere. This obviously called for an amendment to the Election Code of the Kyrgyz Republic that allowed citizens to vote at the place they were actually living at the time of the election, rather than at their place of registration.2 This produced enough votes to amend the Constitution.